Electric Field Response in XLPE to Various Void Sizes and Void Distances to Electrodes (ELEKTRIKA- Journal of Electrical Engineering, 2025)
XLPE is widely used as an insulating material in electrical systems due to its excellent dielectric properties. However, the effectiveness and dependability of the insulation might be severely impacted by the existence of voids inside it. The objective of this research is to simulate the electric field intensity in an XLPE matrix under varying voltages (15 kV, 20 kV, and 25 kV), with a focus on assessing cable aging. The study aims to examine how void size and void location influence the electric field distribution within the XLPE material. Additionally, the research seeks to explore the impact of void presence on stress concentrations and the electric potential drop within the defect area. To achieve these objectives, the study utilizes COMSOL Multiphysics software and the Finite Element Method (FEM) for the simulations. The simulation process considers different void sizes and varying distances between voids and electrodes. The electric field distribution is analyzed under the different voltage conditions to observe the effects of voids on the electric field and potential drop. The study highlighted that void location significantly impacts electric field distribution, with voids positioned closer to high-voltage electrodes resulting in higher electric field intensities, while voids located farther away exhibit lower field intensities. Additionally, the comparison between the absence and presence of voids showed that voids create stress concentrations, resulting in a more drastic drop in electric potential within the void-defect area. The examination of void location on electric field intensity has revealed the significant impact of void positioning on the distribution of electric fields, emphasizing the importance of precise insulation design and void detection strategies.
Keywords: XLPE; Electric field Intensity; Void